Evaluation of Legal Aid Service Quality and Supervision in Indonesia and Malaysia - Tri Utami, Nurani Ajeng; Raharjo, Agus; Prayitno, Kuat Puji; Wahyudi, Setya; Bintoro, Rahadi Wasi; Ismail, NoorFajri (Journal of Human Rights, Culture and Legal System, 2025)
In Indonesia's justice system, the poor are a marginalized group whose economic hardships hinder the ability to understand legal information and access legal services. To address this issue, Indonesia initiated a state-funded Legal Aid Program in 2011 leading to a surge of accreditation applications from Legal Aid Organizations (OBHs) seeking access to the funding. Therefore, this research aimed to examine the quality of legal aid services provided by state-funded OBH and to propose an ideal model for monitoring the quality of the services. A conceptual and comparative approach to relevant regulations was used and supported by primary data from interviews with Legal Aid Extension Officers at the Ministry of Law and Human Rights as well as Advocates affiliated with the organizations. The results showed that the quality of legal aid services in Indonesia remained poor due to the indication of double funding where both the Ministry and Regional Governments allocated budgets for the same services. Additionally, some OBH advocates still charge service fees and failed to provide assistance according to the service standards. Malaysia's legal aid system also showed better quality management as it integrated both state and private sector participation while assigning the assessment of legal aid eligibility to the Director of Legal Aid rather than the service-providing organizations. This approach led to more accurate implementation and better oversight. Furthermore, the research found an urgent need for integrated supervision of legal aid services in Indonesia, along with strict sanctions for both OBH and advocates who violated service standards. Malaysia’s firm approach to monitoring and eligibility determination served as a model worth considering.